Optimization and Characterization of Self Nano Emulsifying Drug Delivery System (SNEDDS) Naringenin Components with D-Optimal Mixture Design Method and Anti-Aging Test In Vivo - Taena, Adriani; Kuncahyo, Ilham; Sunarni, Titik (PT FORMOSA CENDEKIA GLOBAL, 2024)
Naringenin (5,7-dihydroxy-2-(4-hydroxyphenyl) chroman-4-one) is one of the flavanone aglycone compounds that has the main activity as an antioxidant. The purpose of this study was to determine the optimum formula and characterization of naringenin SNEDDS and to see the anti-aging activity of the optimum formula of naringenin SNEDDS. The optimum formula of naringenin SNEDDS was obtained by a combination of oil components, surfactants and cosurfactants (miglyol, tween 80 and transcutol) using the D-optimal mixture design method. The characteristics of naringenin SNEDDS are seen based on parameters such as drug loading, emulsification time, % transmittance, particle size analyzer (PSA) and zeta potential. The results of the optimum formula characterization test of naringenin SNEDDS obtained drug loading of 2.004507 mg/5 ml, emulsification time of 13.07 seconds, percent transmittance of 85.1%, particle size of 78.76 nm and zeta potential of -8.14 mV. Based on the results of the characteristics obtained from the optimum formula, the naringenin SNEDDS preparation meets the characteristics of good SNEDDS and has the potential to be developed into a drug preparation.